Suitability of natural and chemically modified peat as a sorbent material for mining water purification in small-scale pilot systems. Issue 7 (21st March 2022) - Heiderscheidt, Elisangela; Leiviskä, Tiina; Campos Lopez, Felipe; Tesfamariam, Axumawit; Postila, Heini
ABSTRACT: In this study, the suitability of natural peat (Nat-Peat) and HCl-modified peat (M-Peat) as a sorbent for purification of mining water was evaluated in two different small-scale pilot systems: a continuous stirred tank reactor (CSTR) and a horizontal flow filter (HFF). The effect of process parameters (peat type, peat dose, mixing time, mixing intensity) on metal (metalloid) removal in the CSTR system was also investigated. In the CSRT, Nat-Peat achieved higher removal of Ni (<80%) and As (∼61%) than M-Peat (72% and 26% for Ni and As, respectively). In the HFF, Nat-Peat achieved slightly lower maximum removal of Ni (<96%) than M-Peat (<98%) and higher removal of As and Sb (<87% and 8%) than M-Peat (<35% and 7%). Thus, chemical modification (HCl) of peat did not improve its affinity for metal and metalloids. Among the process parameters studied, peat dose exerted the strongest effect on residual concentrations of Ni, As and Sb. Higher removal of Ni and As was achieved in treatment combinations involving high peat dose (2 g/L), mixing time (60 min) and mixing intensity (300 rpm), but the effect of increasing level of these factors was not linear. This study showed that peat can be a viable sorbent material in CSTR systems (followed by sedimentation) if sorbent particle removal can be improved. Use of peat in HFF systems is not viable, due to its inability to cope with large water volumes. GRAPHICAL ABSTRACT: UF0001